2021
DOI: 10.2174/1871523022666221213155905
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Its Role in Reducing the Expression of Pro-inflammatory Cytokines in Osteoarthritis

Abstract: Osteoarthritis is the most common human joint disease in the world. It is also one of the most common skeletal muscle defects, destructive joint changes, and the leading cause of disability and reduced quality of life. Destructive changes in inflammatory joints are associated with a range of biochemical events, including the overproduction of inflammatory cytokines. Cytokines are protein compounds that play an essential role in causing and regulating inflammation. A balance between pro-inflammatory and anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 140 publications
1
3
0
Order By: Relevance
“…The proposed binding by Qe at the allosteric linker site, in all likelihood, affects the catalytic activity of the RNase site (as seen by the IC 50 values) but does not directly impose on dimer formation. This inhibitory activity of Qe towards hIRE1 RNase could be consistent with several physiological effects of Qe, for instance, regarding its anti-inflammatory properties [20][21][22][23] , provided that IRE1 signaling is pro-inflammatory 24,25 . Although Qe has been associated with numerous health benefits related to inflammation and immune function 26 , Boots et al 27 introduced the concept of the "quercetin paradox" in their study using rat lung epithelial (RLE) cells.…”
Section: Discussionsupporting
confidence: 79%
“…The proposed binding by Qe at the allosteric linker site, in all likelihood, affects the catalytic activity of the RNase site (as seen by the IC 50 values) but does not directly impose on dimer formation. This inhibitory activity of Qe towards hIRE1 RNase could be consistent with several physiological effects of Qe, for instance, regarding its anti-inflammatory properties [20][21][22][23] , provided that IRE1 signaling is pro-inflammatory 24,25 . Although Qe has been associated with numerous health benefits related to inflammation and immune function 26 , Boots et al 27 introduced the concept of the "quercetin paradox" in their study using rat lung epithelial (RLE) cells.…”
Section: Discussionsupporting
confidence: 79%
“…This dual effect of S. adstringens may explain its significant impact on wound healing, where a rapid inflammatory response is needed to prevent infections while also promoting tissue regeneration. These effects of S. adstringens are possibly associated with its chemical matrix rich in bioactive components described in Table 1, which have anti-inflammatory and cytokine-modulating action previously described in the literature [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Since this study aimed to investigate the modulatory effect of pro-and anti-inflammatory cytokines by S. adstringens on macrophages, a search was also conducted for scientific reviews indicative of the anti-inflammatory activity of each of the main bioactive molecules identified in the extract. [25]. Reduction in the expression of proinflammatory cytokines in osteoarthritis [26].…”
Section: S Adstringens's Extract Characterizationmentioning
confidence: 99%
“… 52 In addition, mounting in vivo and in vitro experiments have found that quercetin and kaempferol not only down-regulates matrix degrading protease and inflammatory mediators in the OA-CH model but also promotes cartilage anabolic factor production and relieves cartilage degradation and inflammation in the OA rat model. 53–55 …”
Section: Discussionmentioning
confidence: 99%